2015
DOI: 10.1590/2446-4740.0805
|View full text |Cite
|
Sign up to set email alerts
|

The influence of subcutaneous fat in the skin temperature variation rate during exercise

Abstract: Introduction: Thermography records the skin temperature, which can be influenced by: muscle mass and subcutaneous fat layer. Thus, the aim of this study was to investigate the influence of subcutaneous fat layer in the skin temperature variation rate, during exercise. Methods: This is a short-longitudinal study that involved 17 healthy male trained volunteers. Volunteers were divided in two groups. The first called GP1 with nine volunteers (biceps brachii skinfold thickness < 4 mm) and the second called GP2 wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
10
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 19 publications
2
10
0
2
Order By: Relevance
“…Another research investigated the difference of skin temperature in the abdominal region between obese and normal weight groups, and the correlation between abdominal skin temperature and body fat percentage was 0.545, while the abdominal skin temperature of obese group was lower than in the normal weight group (Savastano et al, 2009). Similar relationships were shown by Neves et al who observed that subjects with lower subcutaneous fat layer had a higher skin temperature variation rate during exercise than those with a thicker subcutaneous fat layer (Neves et al, 2015).…”
Section: Discussionsupporting
confidence: 56%
“…Another research investigated the difference of skin temperature in the abdominal region between obese and normal weight groups, and the correlation between abdominal skin temperature and body fat percentage was 0.545, while the abdominal skin temperature of obese group was lower than in the normal weight group (Savastano et al, 2009). Similar relationships were shown by Neves et al who observed that subjects with lower subcutaneous fat layer had a higher skin temperature variation rate during exercise than those with a thicker subcutaneous fat layer (Neves et al, 2015).…”
Section: Discussionsupporting
confidence: 56%
“…Regarding future arm and forearm muscle studies, it is recommended to explore the accuracy of thermographic evaluation of muscular activity and to use the subcutaneous fat layer as a co-variable, since it affects heat transfer rate from the muscle to the skin surface (Neves et al, 2015b;Novotny et al, 2015). Further analysis of the early detection of sore muscles, through thermal imaging, is advised, due to its potential in lowering the chances of athletes suffering from injuries caused by over-exercised muscles in the sport setting (Al-Nakhli et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…The TISEM points, which were poorer in the literature appraised were: the specification of the time between setting the camera on and the images collection for avoiding the startup drift, the mention of the time of the day that the images were taken, and the drying method used for the skin in the situation that required it, which in most of these applications was not the case. The level of evidence of statistics overall was poor, most research works consisted in small samples, some lacked a control group, 8 papers (Neves et al, 2015b(Neves et al, , 2016Trentin et al, 2012;Chudecka and Lubkowska, 2012;Ratovoson et al, 2013;Chang et al, 2015;Haluzan et al, 2015;Boguszewski et al, 2015) did not presented any statistics and Neves et al (Neves et al, 2015a) presented the wrong statistics.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…• Psychosomatic constitution (Prakriti): Ayurveda has described that the quantity and odor of sweat depends upon psychosomatic constitution of an 27 , so in obese the major site of heat loss is palm and sole due to presence of arteiovenous anastomoses. Degree of thermal insulation is positively correlated to degree of obesity 28 . Ayurveda has also given similar thought that in obesity there is Vata Vriddhi (~ autonomic dysfunction) and Srotoavrodha due to excess deposition of fat resulting in the augmentation of digestive fire and more appetite 29 , more intake of food and thus more formation of Aahara Mala i.e.…”
Section: Factors Affecting Sweatmentioning
confidence: 96%